The Interactive Effects of Behavioral Integrity and Procedural Justice on Employee Job Tension - Andrews, Martha C. (Journal of business ethics, 2015)
Using data collected from 280 full-time employees from a variety of organizations, this study examined the effects of employee perceptions of the behavioral integrity (BI) of their supervisors on job tension. The moderating effect of procedural justice (PJ) on this relationship also was examined. Substitutes for leadership theory (Kerr and Jermier, 1978) and psychological contract theory (Rousseau, Empl Responsib Rights J 2:121–139, 1989) were used as the theoretical foundations for the hypothesized relationships. Results indicated a negative relationship between BI and job tension. PJ moderated this relationship such that it was weakened under conditions of high PJ. Implications for research and managers are discussed.